A world alone: Masculinities, humiliation and aggrieved entitlement on an incel forum. (4th April 2022) - Thorburn, Joshua; Powell, Anastasia; Chambers, Peter
Abstract: An emerging body of criminological research has sought to investigate the 'incels' movement. This article explores the construction of masculinities, gender and violence in a popular incel online forum. Here, we discuss results from a digital ethnography incorporating qualitative analysis of user posts, with a focus on three key overarching themes, namely: biological determinism, masculine humiliation and hierarchical gender relations. Our analysis draws on concepts such as hegemonic and hybrid masculinities (Demetriou 2001; Connell 2005; Bridges and Pascoe 2014), as well as Kimmel's (2013) notion of 'aggrieved entitlement', to further develop understandings of the complexity of users' framings of gender and masculine identity within the forum. Implications for future research in the field are then discussed.